Pendampingan Pemanfaatan Sarana Pemasaran Digital di Desa Banjarsari Kapanewon Samigaluh Kulon Progo - Marausna, Gaguk; Putra, Ikbal Rizki; Bukhori, Muhammad Luqman; Rachmawati, Desiana; Susastriawan, Anak Agung Putu; Rahayu, Suparni Setyowati; Mulyaningsih, Sri (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
Banjarsari Village has several advantages that can be used as a tourist destination. Assistance activities aim to make this tourism potential is better known to the public, it will allow the growth of tourists so that it can increase income. This community service program was carried out in November 2023 through identifying problems, designing solutions and implementing solutions in the form of outreach and training in managing websites and social media. The social media recommended for use as marketing media are Tiktok, Instagram and Youtube. This activity encourages the people of Banjarsari Village to be more familiar with digital media so they can manage social media and websites with interesting content to promote tourism in Banjarsari Village. Participants know the function and use of websites and social media as digital marketing tools regarding Banjarsari Village tourism. Marketing MSME products via social media can increase partner sales by 41.67% for average sales per week.